CTmax is repeatable and doesn’t reduce growth in zebrafish - Rachael Morgan (Nature Portfolio, 2018)
Abstract Critical thermal maximum (CTmax) is a commonly and increasingly used measure of an animal’s upper thermal tolerance limit. However, it is unknown how consistent CTmax is within an individual, and how physiologically taxing such experiments are. We addressed this by estimating the repeatability of CTmax in zebrafish, and measured how growth and survival were affected by multiple trials. The repeatability of CTmax over four trials was 0.22 (0.07–0.43). However, CTmax increased from the first to the second trial, likely because of thermal acclimation triggered by the heat shock. After this initial acclimation response individuals became more consistent in their CTmax, reflected in a higher repeatability measure of 0.45 (0.28–0.65) for trials 2–4. We found a high innate thermal tolerance led to a lower acclimation response, whereas a high acclimation response was present in individuals that displayed a low initial CTmax. This could indicate that different strategies for thermal tolerance (i.e. plasticity vs. high innate tolerance) can co-exist in a population. Additionally, repeated CTmax trials had no effect on growth, and survival was high (99%). This validates the method and, combined with the relatively high repeatability, highlights the relevance of CTmax for continued use as a metric for acute thermal tolerance.